Realizing the SDGs through Zakat: The Maqāsid al-Syari'ah Perspective at Zakat Institutions in Indonesia - Isman, Ainul Fatha; Mansyur, Abdurrahman; Wardani, Ali (Muslim Business and Economics Review, 2023)
Zakat is one of the essential instruments in sustainable development, and its implementation is considered relevant to the concept of Maqāṣid al-Sharī'ah, which aims to achieve benefit. The purpose of this study is to analyze the realization of Zakat on the achievement of SDGs from the perspective of Maqāṣid al-Sharī'ah, which includes hifẓ al-din, hifẓ al-nafs, hifẓ al-māl, hifẓ al-naṣl and hifẓ al-aql. This research is descriptive quantitative research with horizontal analysis and comparative analysis. The sampling technique in this study is purposive sampling. The research samples are BAZNAS, LAZ Rumah Zakat, LAZ Dompet Dhuafa, LAZ Inisiatif Zakat Indonesia, LAZ Yatim Mandiri, LAZ The Panti Yatim Indonesia Foundation, LAZ Baitulmal Muamalat and LAZ Mizan Amanah. The data collected in this study were from the Annual Report and the financial reports of zakat institutions from 2016-2019. The results show that all zakat institutions have realized Zakat on the achievement of SDGs from the Maqāṣid al-Sharī'ah perspective, which includes hifẓ al-dīn, hifẓ al-nafs, hifẓ al-māl, hifẓ al-naṣl and hifẓ al-aql. Zakat institutions have realized Zakat on the achievement of SDGs from a Maqāṣid al-Sharī'ah perspective which includes hifẓ al-dīn, hifẓ al-nafs, hifẓ al-māl, hifẓ al-naṣl, and hifẓ al-aql. Overall, the realization of Zakat on SDGs from the perspective of Maqāṣid al-Sharī'ah is most significant in the hifẓ al-māl dimension. The most dominant LAZ Rumah Zakat is the realization of Zakat from the hifẓ al-māl perspective on the SDGs. Meanwhile, from the standpoint of hifẓ al-naṣl, hifẓ al-nafs, and hifẓ al-aql towards SDGs is greatest at Laz Dompet Dhuafa. As for the realization of Zakat on the hifẓ al-din dimension, the highest is BAZNAS. Thus, the Zakat is allocated more to the SDGs to end poverty. This research implies that zakat institutions remain consistent in realizing their funds towards sustainable development goals from the perspective of Maqāṣid al-Sharī'ah and increasing their performance to make a significant contribution to welfare.